Trans-cis photoisomerization in nanostructured floating layers and x-ray diffraction study of Langmuir-Schaefer films of nonyloxypheylazocinnamic acid. (24th May 2017) - Pisani, M.; Maiorova, L. A.; Francescangeli, O.; Fokin, Dm. S.; Nikitin, K. S.; Burmistrov, V. A.; Kuvshinova, S. A.; Mengucci, P.; Koifman, O. I.
ABSTRACT: Azo-functionalised materials are of special interest due to their photochromic nature, i.e. reversible trans – cis isomerisation upon photoirradiation. The structure and properties of Langmuir monolayers of nonyloxyphenylazocinnamic acid (NOPACA) with and without exposure to UV-irradiation were studied. The NOPACA floating layer structure was determined by using a quantitative method of compression isotherm analysis. The results showed that the structure of two dimensional face-on M -nanoaggregates, the stable structural elements of floating monolayers, changes when exposed to UV-irradiation. Langmuir-Schaefer films of NOPACA were prepared by deposition of floating layers and studied using X-ray diffraction technique.